PENGGUNAAN POSTER INFOGRAFIS PADA PEMBELAJARAN IPA MATERI SISTEM PERNAPASAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP KELAS VIII - Saputra, Ardiansyah Dharma; Hidayati, Siti Nurul (Program Studi S1 Pendidikan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2023)
This research was conducted to determine the increase in student learning outcomes using infographic posters in natural science learning. This type of research used pre-experimental one group pretest posttest design. The research subjects used in this study were 21 students of class VIII-H. Data collection techniques in this research used observation, questionnaires, and tests. The research instrument consisted of learning implementation observation sheets, student response questionnaire sheets, student knowledge test sheets. The results of this study are: (1) The implementation of the natural science learning on the respiratory system material as a whole has been carried out in the